2018
DOI: 10.2147/dddt.s151511
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Neuregulin-1/ErbB signaling in the hippocampus of rats after administration of doxorubicin

Abstract: ObjectiveLong-term use of doxorubicin (Dox) can cause neurobiological side effects associated with depression, but the underlying mechanisms remain equivocal. While recent evidence has indicated that Neuregulin-1 (NRG1) and its ErbB receptors play an essential role in neural function, much is still unknown concerning the biological link between the NRG1/ErbB pathway and the Dox-induced neurotoxicity. Therefore, we examined the protein expression of NRG1 and ErbB receptors in the hippocampus of rats following D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…The results from the present study also indicated that DOX suppressed activation of the downstream Akt and Erk pathway, which was detected by the phosphorylation of its mediators Erk and Akt, respectively. This result was in accordance with previous findings (32). Hang et al (11) also demonstrated that BDNF/TrkB signaling is necessary in preventing cardiotoxicity following administration of DOX.…”
Section: Discussionsupporting
confidence: 93%
“…The results from the present study also indicated that DOX suppressed activation of the downstream Akt and Erk pathway, which was detected by the phosphorylation of its mediators Erk and Akt, respectively. This result was in accordance with previous findings (32). Hang et al (11) also demonstrated that BDNF/TrkB signaling is necessary in preventing cardiotoxicity following administration of DOX.…”
Section: Discussionsupporting
confidence: 93%
“…The novelty-suppressed feeding test (NSFT) was adapted from previous study [15]. Before testing, rats were fasted for 24 h. The rats were placed in an open field (75 × 75 × 40 cm).…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Oxytocin improved depression symptom by down-regulating c-fos protein and by inhibiting the ERK pathway as well [66]. (4) The ErbB pathway was also associated with depression by adjusting neuregulin and affecting downstream Akt and ERK signaling pathways [67,68]. EGF and VEGF were parts of the ErbB family and were associated with nerve growth and nutrition [69].…”
Section: Discussionmentioning
confidence: 99%